2013
DOI: 10.1590/s0004-27492013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity after refractive lens exchange with a multifocal diffractive aspheric intraocular lens

Abstract: Purpose: To evaluate distance and near contrast sensitivity (CS) under photopic and mesopic conditions before and after refractive lens exchange (RLE) and implantation of the aspheric AcrySof ® ReSTOR ® (SN6AD3 model) intraocular lens (IOL). Methods: Seventy-four eyes of 37 patients after RLE underwent bilateral implantation with the aspheric AcrySof ReSTOR IOL. The patient sample was divided into myopic and hyperopic groups. Monocular uncorrected visual acuity at distance and near (UCVA and UCNVA, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In addition, many studies have compared mfIOLs with different optic designs and a high variability of results have been published with some authors concluding that diffractive IOLs showed better CSF outcomes than refractive IOLs (4,21) and vice versa (22,23). Another report (24) showed no differences between the preoperative and postoperative CSF after refractive lens exchange with implantation of a bifocal IOL. Due to the high variability of the CSF, our research group has compared several mfIOLs with different optic designs in order to ascertain which IOL provided the highest LMCSF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have compared mfIOLs with different optic designs and a high variability of results have been published with some authors concluding that diffractive IOLs showed better CSF outcomes than refractive IOLs (4,21) and vice versa (22,23). Another report (24) showed no differences between the preoperative and postoperative CSF after refractive lens exchange with implantation of a bifocal IOL. Due to the high variability of the CSF, our research group has compared several mfIOLs with different optic designs in order to ascertain which IOL provided the highest LMCSF.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria by which some clinicians consider refractive lens exchange as a treatment for presbyopia include stage 2 with increased ocular scatter (2,3) , high myopia (21) , hyperopia (22) , and patients with stage 1 associated with reduced visual quality under low light conditions. (23) However, this decision must consider the risks in performing cataract surgery, including retinal detachment, macular edema, and choroidal effusion. (22) Importantly, there is a percentage increase in these complications when associated with high myopia and high hyperopia.…”
Section: A Staging Proposal For Dysfunctional Lens Syndromementioning
confidence: 99%
“…(22) Importantly, there is a percentage increase in these complications when associated with high myopia and high hyperopia. (22,23) CONCLUSION While the concept of dysfunctional lens syndrome is now commonly recognized, a standard and universally accepted staging system has yet to be established. In the staging system proposed in this review, transparency and presbyopia are independent factors, but in advanced stages, they can occur concomitantly.…”
Section: A Staging Proposal For Dysfunctional Lens Syndromementioning
confidence: 99%